Mitochondria-Targeted Delivery of Camptothecin Based on HPMA Copolymer for Metastasis Suppression - Xiaoli Yi; Yue Yan; Xinran Shen; Lian Li; Yuan Huang (MDPI AG, 2022)
Poor anti-metastasis effects and side-effects remain a challenge for the clinical application of camptothecin (CPT). Mitochondria can be a promising target for the treatment of metastatic tumors due to their vital roles in providing energy supply, upregulating pro-metastatic factors, and controlling cell-death signaling. Thus, selectively delivering CPT to mitochondria appears to be a feasible way of improving the anti-metastasis effect and reducing adverse effects. Here, we established a 2-(dimethylamino) ethyl methacrylate (DEA)-modified N-(2-hydroxypropyl) methacrylamide (HPMA) copolymer-CPT conjugate (P-DEA-CPT) to mediate the mitochondrial accumulation of CPT. The mitochondria-targeted P-DEA-CPT could overcome multiple barriers by quickly internalizing into 4T1 cells, then escaping from lysosome, and sufficiently accumulating in mitochondria. Subsequently, P-DEA-CPT greatly damaged mitochondrial function, leading to the reactive oxide species (ROS) elevation, energy depletion, apoptosis amplification, and tumor metastasis suppression. Consequently, P-DEA-CPT successfully inhibited both primary tumor growth and distant metastasis in vivo. Furthermore, our studies revealed that the mechanism underlying the anti-metastasis capacity of P-DEA-CPT was partially via downregulation of various pro-metastatic proteins, such as hypoxia induction factor-1α (HIF-1α), matrix metalloproteinases-2 (MMP-2), and vascular endothelial growth factor (VEGF). This study provided the proof of concept that escorting CPT to mitochondria via a mitochondrial targeting strategy could be a promising approach for anti-metastasis treatment.